Applications of generative artificial intelligence to influence climate change decisions - Daniel Richards; David Worden (npj Climate Action)
Climate change decision making is complex and subject to attempted influence from actors with diverse agendas. Generative artificial intelligence (GenAI) technologies are emerging as new tools in influencing public discourses and decisions, which will increasingly be applied to climate change issues. We define a typology of influence of climate decisions by GenAI, present example cases, and highlight urgent research needs in this field.